(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Skin diseases comprise a large proportion of patients approaching clinics and hospitals. Arka taila is an Ayurvedic preparation for Kandu (itching), Pama (scabies), Vicharchika (eczema). It is mentioned in various classical books of Ayurveda like Sharangadhara samhita vangasena samhita etc. To make the Taila form, it was decided to convert it in to cream form without compromising on its efficacy. In the present study Arka taila was prepared by classical methods and its cream was prepared by modern parameters. Initially 3 litres of Sarshap taila was taken as raw material and yield of Arka Taila was 2.815L. 1.985kg of Arka Cream was prepared from it. The pharmaceutical process reveals that a good quality Arka Taila can be easily prepared by taking caution about various stages occurring during the Sneha-Paka and by paying attention to the Sneha-Siddhi-Lakshanas. Furthermore, preparation of a stable, effective and good consistency emulsion was formulated in the form of Arka cream.